DIGITAL PEDAGOGY IN VOCATIONAL EDUCATION: A SCOPUS-BASED BIBLIOMETRIC ANALYSIS (2016–2025) - Indah Khoerunnisa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The rapid advancement of digital technology has transformed learning practices in vocational education; however, systematic mapping of digital pedagogy research in this field remains limited. This study aims to analyze research trends, intellectual structures, and future directions of digital pedagogy in vocational education through a bibliometric approach. The data were collected from the Scopus database covering the period 2016–2025, resulting in 115 eligible documents. The analysis was conducted using VOSviewer and Biblioshiny through publication productivity analysis, co-citation analysis, keyword co-occurrence analysis, and co-authorship network analysis. The findings reveal a substantial growth in publications on digital pedagogy in vocational education, with an annual growth rate of 53.02%, accelerating during the COVID-19 pandemic and continuing to increase through 2025. Indonesia and Finland emerged as the leading contributors, while Universitas Pendidikan Indonesia was identified as the most productive institutional affiliation. Visualization analysis identified four major thematic clusters: artificial intelligence integration and personalized learning, blended learning and instructional innovation, vocational teachers’ digital competence, and digital divide and educational equity. Furthermore, thematic evolution analysis indicates a shift from conventional e-learning toward immersive technologies and artificial intelligence applications. The study provides a comprehensive overview of the intellectual landscape of digital pedagogy in vocational education and offers valuable insights for researchers, practitioners, and policymakers in developing adaptive, inclusive, and sustainable digital learning strategies. ABSTRAK Perkembangan teknologi digital telah mendorong transformasi pembelajaran pada pendidikan vokasi, namun kajian yang memetakan perkembangan penelitian digital pedagogy secara sistematis masih relatif terbatas. Penelitian ini bertujuan menganalisis tren, struktur intelektual, serta arah perkembangan riset digital pedagogy dalam konteks pendidikan vokasi melalui pendekatan bibliometrik. Data penelitian diperoleh dari database Scopus periode 2016–2025 dengan total 115 dokumen yang memenuhi kriteria inklusi. Analisis dilakukan menggunakan perangkat lunak VOSviewer dan Biblioshiny melalui tahapan analisis produktivitas publikasi, ko-sitasi, kemunculan bersama kata kunci (co-occurrence), dan jaringan kolaborasi penulis (co-authorship). Hasil penelitian menunjukkan bahwa publikasi terkait digital pedagogy dalam pendidikan vokasi mengalami pertumbuhan yang sangat signifikan dengan tingkat pertumbuhan tahunan sebesar 53,02%, yang meningkat pesat sejak pandemi COVID-19 dan terus berkembang hingga tahun 2025. Indonesia dan Finlandia tercatat sebagai negara dengan kontribusi publikasi terbesar, sedangkan Universitas Pendidikan Indonesia menjadi afiliasi yang paling produktif. Analisis visualisasi mengidentifikasi empat kluster tematik utama, yaitu integrasi kecerdasan buatan dan personalisasi pembelajaran, pembelajaran campuran dan inovasi instruksional, kompetensi digital guru vokasi, serta kesenjangan digital dan pemerataan akses pendidikan. Selain itu, evolusi tema penelitian menunjukkan pergeseran fokus dari e-learning konvensional menuju pemanfaatan teknologi imersif dan kecerdasan buatan. Temuan ini memberikan gambaran komprehensif mengenai perkembangan digital pedagogy dalam pendidikan vokasi serta menjadi dasar bagi peneliti, praktisi, dan pembuat kebijakan dalam merancang strategi pembelajaran digital yang lebih adaptif, inklusif, dan berkelanjutan.